Product Design and Development - Ulrich, Karl T.; Eppinger, Steven D. (New York, NY : McGraw-Hill Education, 2020)
Treating such contemporary design and development issues as identifying customer needs, design for manufacturing, prototyping, and industrial design, Product Design and Development by Ulrich and Eppinger presents in a clear and detailed way a set of product development techniques aimed at bringing together the marketing, design, and manufacturing functions of the enterprise. The integrative methods in the book facilitate problem solving and decision making among people with different disciplinary perspectives, reflecting the current industry toward designing and developing products in cross-functional teams
Note continued: References and Bibliography -- Exercises -- Thought Questions -- Appendix Design Structure Matrix Example
Includes bibliographical references and index
Keywords: New products -- Decision making -- Methodology -- Case studies; Product design -- Cost effectiveness -- Case studies; Production engineering -- Case studies; Case studies